Disadvantages of the Replacement Ratio Indicator with Calculation of a New Variant of This Indicator: A Case Study of Czech Republic - Stipek, Vladimir (European Scientific Journal, ESJ, 2018)
This article deals with the analysis of the replacement ratio (an indicator of the relation between the average wage and the average pension). This was carried out on the basis of the analysis of pensioners’ consumer baskets and their expenditures. It proposes a more appropriate concept of the so-called real replacement ratio. The replacement ratio is often used for longterm (intergenerational) comparisons of the standard of living of pensioners. Also, the weaknesses of this indicator make such comparisons insufficiently informative. On the other hand, the so-called real replacement ratio takes into account the impact of significant cost items and cost items whose price is rising. As a result, this provides only a comparable standard of living without contributing to the improvement of living standards, for example through consumption expenditures. Examples of these significant cost items are housing, healthcare or transport. As illustrated by the paper, before 1989, the level of these costs was considerably lower, which is not taken into account by the average values of the non-adjusted replacement ratio. The replacement ratio calculated in the usual manner was 41.56% in 2016 and decreased to 33.7% with the use of the real replacement ratio concept.